Nanoconfined water governs polarization‐related properties of self‐assembled peptide nanotubes - Salehli, Ferid; Aydin, Abuzer O.; Chovan, Drahomir; Kopyl, Svitlana; Bystrov, Vladimir; Thompson, Damien; Tofail, Syed A.M.; Kholkin, Andrei (Wiley, 2021)
AbstractDiphenylalanine (FF) demonstrates a robust ability to self‐assemble at the nanoscale forming a variety of structures ranging from nanospheres to nano‐ and microtubes resulting in outstanding functional properties including pyro‐ and piezoelectricity. FF nanotubes mimic the structure of β‐amyloid fibrils characteristic of Alzheimer's disease and thus can serve as a model material in biology and medicine. In this work, we report experimental proof that water trapped inside nanotubes exhibits dielectric properties similar to that of bulk water despite being confined in an ∼1 nm internal cavity. FF peptides thus provide a suitable template for the stabilization of the tetrahedral configuration of bulk water. Several phase transitions were observed via broadband dielectric spectroscopy and differential scanning calorimetry. Of these, two glass transitions at 205 K and 133 K related to different phases of water were found. The presence of α‐relaxation in the so‐called “no man's land” leads to a global glass transition at Tg = 133 K and structural phase transition at 230 K characteristic of tetrahedral water. The characterized collective response of water dipoles to an external electric field renders high pyro‐ and piezoelectric activity and non‐linear optical effects in FF dipeptides, conferring polarization‐dependent functionality to this important class of biomaterials.
Keywords: peptide nanotubes; TA401-492; dielectric spectroscopy; Materials of engineering and construction. Mechanics of materials; nanoconfined water; phase transitions